Support system of making decision on perfection of the construction of vehicles - Гелло, Василь Олександрович (Eastern-European Journal of Enterprise Technologies, 2012)
Informative and formal task definition of development of specialized support system of making decision on perfection of a construction of automobile vehicles is considered, the generalized algorithm of the decision of the task is resulted and program implementation of the offered algorithm on an example of the unit of optimization of a construction of brake system of wheel machines is described.